2021
DOI: 10.1186/s12886-020-01756-8
|View full text |Cite
|
Sign up to set email alerts
|

Two-year outcomes after full-thickness astigmatic keratotomy combined with small-incision lenticule extraction for high astigmatism

Abstract: Background To evaluate clinical outcomes after full-thickness astigmatic keratotomy (FTAK) combined with small-incision lenticule extraction (SMILE) in eyes with high astigmatism. Methods This study comprised 75 eyes of 43 patients with over 4.0 diopters (D) of astigmatism who were treated with SMILE after FTAK. Visual acuities and refractive measurements were evaluated at 1 month after FTAK, and 1, 6, 12, and 24 months after SMILE. Vector analysis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Therefore, we opted for initially unpaired, unopened pFAKs to negate such rare documented problems as infection, epithelial down growth or wound gape [18][19][20][21] . Arcuate keratotomies have also been shown to result in increase of higher order aberrations and by not opening them we aimed to avoid issues associated with this [28] . Although we did not perform postoperative aberrometry, which is a limitation of this study, our visual and patient reported outcome measures [12] did not raise any concerns to suspect any significant effect from higher order aberrations.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we opted for initially unpaired, unopened pFAKs to negate such rare documented problems as infection, epithelial down growth or wound gape [18][19][20][21] . Arcuate keratotomies have also been shown to result in increase of higher order aberrations and by not opening them we aimed to avoid issues associated with this [28] . Although we did not perform postoperative aberrometry, which is a limitation of this study, our visual and patient reported outcome measures [12] did not raise any concerns to suspect any significant effect from higher order aberrations.…”
Section: Discussionmentioning
confidence: 99%